Reading through the style in John Keats’s “On the Grasshopper and Cricket” - Ariya Jati (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2026)
This article intends to delve into the style in John Keats’s “On the Grasshopper and Cricket”, probing its versification, diction, as well as imagery and figures of speech. This Keats’s sonnet will be studied using Gabriele Griffin’s view on a textual analysis, and this study adopts S.H Burton’s concept of style in relation to ADP Briggs’s that of English sonnets. The analysis results mainly in the poetic prosody of the sonnet, and it can be concluded that although the sonnet is deemed less renowned, it distinctively designates the poet’s stylistic development. After all, it is recommended that further research produce, among others, musical annotation to bridge sonic gaps.